Pengaruh Besar Ukuran Partikel Terhadap Sifat – Sifat Tablet Metronidazol - Maria Dona Octavia; Auzal Halim; Rika Indriyani (STIFARM Padang, 2012)
The influence of particle size toward the characteristics of Metronidazole tablets has been studied. Metronidazole that is used for first formua is not crushed, for the second formula is used Metronidazole powder cruhed for 30 minutes, and for the third formula is used Metronidazole powder that is crushed for 3 hours. The crushing process of the powder is done by using Ball mill. The result is analysed by SEM, DTA, FT IR, and particle distribution. DTA data (mettler Toledo) shows the changing of thermodynamic characteristics that occurs when the sample is given heat energy in form of melting shown by endoterm. From the three formula are made Metronidazole tablets by using wet granulation. The formulations of Metronidazole use mucilago gelatin as a binder, lactose as excipients, amylum as desintegrant and aerosil as a lubricant. Tablet evaluation involves the same size, same weight, the strength determining of level and dissolution. Dissolution test is done by using basket method and the level determined by the method of UV Spectrophotometer at the maximum absorption wavelength of 276.5 nm in HCl 0,1 N. The result of the assay formula 1 is 82,6248%, the formula 2 is 87.3086% and the formula 3 is 95.7037%. Result of dissolution measurement at 60 minutes showed that the average dissolution is 47.902%, 68,584% and 69.320%. The dissolution profile test uses HCl 0,1 N. The analysis of dissolution profile is done by the equality orde 0, orde 1, Higuchi and Korsmeyer peppas. Dissolution profile of Metronidazole tablets approach to Korsmeyer peppas.